The Marriage Checkup: Adapting and Implementing a Brief Relationship Intervention for Military Couples. Issue 4 (November 2016) - Cigrang, Jeffrey A.; Cordova, James V.; Gray, Tatiana D.; Najera, Elizabeth; Hawrilenko, Matt; Pinkley, Crystal; Nielsen, Matthew; Tatum, JoLyn; Redd, Kristen
Abstract: Given the significant negative impact of relationship distress on the health and well being of members of the military, preventative and accessible care is needed in order to provide crucial relationship support to service members and their families. This paper presents the rationale, key considerations, and feasibility for adapting the Marriage Checkup (MC), a brief intervention for enhancing marital resiliency, for use by internal behavioral health consultants (IBHCs) working in an integrated primary care clinic serving an active duty military population. We detail the adapted MC protocol, which was revised to contain military-centric content and fit into the fast-paced environment of primary care (e.g., streamlined to fit within three 30-minute appointments). IBHCs working in primary care were trained to offer the intervention at two air force bases. Twenty couples and 1 individual have completed the MC and a 1-month follow-up assessment. The MC intervention appeared to be well-received by both couples and IBHCs. In this paper, we provide specific guidance for clinicians and providers who are interested in integrating the Marriage Checkup into their practice. Highlights: Community problems faced by the military are linked to marriage relationships. Despite the costs of chronic marital distress, very few couples seek therapy. We piloted a brief marital intervention for primary care that may reach couples early. Results provided preliminary evidence that the protocol improves relationship health.